Activation of Human Platelets Causes Post-translational Modifications to Cytoplasmic Dynein - Rothwell, Stephen W; Calvert, Valerie S (Thrombosis and Haemostasis, 1997)
In our studies of human platelets we have detected the presence of the molecular motors kinesin and dynein. Dynein is present at a concentration (0.8 μg/g tissue) that is approximately 1/3 the concentration reported for neuronal tissue. Immunofluorescence microscopy of resting platelets shows that, while platelet microtubules are arranged in coiled hoops forming the marginal band in the cortical region of the platelet, dynein is distributed in a pattern of punctate staining throughout the cytoplasm of the platelets. Fractionation of unactivated platelets shows that dynein partitions to the soluble fraction. Stimulation of platelets with thrombin, ADP or epinephrine causes a partial translocation of dynein from the soluble fraction to the particulate fraction with thrombin being the most efficient agent at promoting this shift. Dynein intermediate chain recovered in the soluble fraction of disrupted platelets following activation displays a transient, time-dependent phosphorylation. In contrast, dynein intermediate chain recovered in the particulate fraction shows decreased phosphorylation. These results indicate that human platelets contain a complex microtubule-based system of motor proteins that is an integral part of the physiological changes occurring during platelet activation.